2014
DOI: 10.1148/rg.344125202
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging–based Diagnosis and Classification of Meniscal Tears

Abstract: Magnetic resonance (MR) imaging is currently the modality of choice for detecting meniscal injuries and planning subsequent treatment. A thorough understanding of the imaging protocols, normal meniscal anatomy, surrounding anatomic structures, and anatomic variants and pitfalls is critical to ensure diagnostic accuracy and prevent unnecessary surgery. High-spatial-resolution imaging of the meniscus can be performed using fast spin-echo and three-dimensional MR imaging sequences. Normal anatomic structures that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
155
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(171 citation statements)
references
References 77 publications
2
155
0
14
Order By: Relevance
“…The menisci were evaluated on the basis of the diagnostic criteria according to Nguyen [15] and De Smet [16]. A tear was diagnosed according to the following criteria: Distortion of the meniscus or a signal increase reaching the joint surface on at least two images with a slice thickness of 3 mm.…”
Section: Evaluating the Mri Scansmentioning
confidence: 99%
“…The menisci were evaluated on the basis of the diagnostic criteria according to Nguyen [15] and De Smet [16]. A tear was diagnosed according to the following criteria: Distortion of the meniscus or a signal increase reaching the joint surface on at least two images with a slice thickness of 3 mm.…”
Section: Evaluating the Mri Scansmentioning
confidence: 99%
“…Uzaysal çözünürlük diz için yapılmış sargı kullanımı, büyük matriks, küçük FOV ve ince kesit kalınlığı ile iyileştirilebilir. Kullanılabilecek tipik parametreler; <16 cm FOV, en az 192 × 256 matriks (faz kodlama x frekans kodlama) ve 3-4 mm kesit kalınlığı olmalıdır [1]. Konvansiyonel spin eko (SE) ve hızlı spin eko sekanslar (FSE) (kısa ETL (<5) ve uzun bant aralığında) karşı-laştırıldığında, bu ikisinin meniskal yırtıkları saptama oranında farklılık olmadığı ifade edilir.…”
Section: Teknikunclassified
“…Konvansiyonel spin eko (SE) ve hızlı spin eko sekanslar (FSE) (kısa ETL (<5) ve uzun bant aralığında) karşı-laştırıldığında, bu ikisinin meniskal yırtıkları saptama oranında farklılık olmadığı ifade edilir. 2B ve 3B FSE teknikleri yırtıkları hemen hemen benzer doğrulukta saptamakla birlikte özellik-le kökü ilgilendiren lateral menisküs yırtıkları söz konusu olduğunda 3B FSE görüntülemenin düşük duyarlılığından bahsedilir [1]. Klasik olarak meniskal yırtık tanısında PD sekansının kullanılmasının T2-a görüntülere tercih edilmesi gerekliliği salık verilir [1].…”
Section: Teknikunclassified
“…Furthermore meniscal injuries impose undue load and stress on the adjacent articular cartilage, predisposing the articular cartilage to damage and thus increasing the risk of early onset of osteoarthritis [2]. Research has demonstrated that injuries which occur within avascular regions of the menisci do not heal spontaneously [3].…”
Section: Introductionmentioning
confidence: 99%
“…Arthroscopy is widely considered the gold standard in the assessment of meniscal injuries, with evidence suggesting magnetic resonance imaging (MRI) is the most accurate non-invasive tool for detecting meniscal injuries [2]. The diagnostic value of MRI has however been questioned, particularly when used in isolation [6].…”
Section: Introductionmentioning
confidence: 99%